Relationship between Religiosity and Self-Efficacy among Patients with Cardiovascular Disorders: Field Study at the Center CHU Hospital Saadna Abdel Nour, Setif Algeria - Korrichi Fayçal; Jabali Nouredinne (Sultan Qaboos University, 2015)
The study aims to put under scrutiny the existing links between the behavior of religiosity and self-efficacy. Gender and education level were used as additional independent variables to test if they have effect on religiosity and self-efficacy. The study relied on data from 62 persons (39 males and 23 females). SPSS 18 was used to analyze data (means and standard deviations, correlation, t-test and ANOVA). The results of the study revealed a significant correlation between religiosity and self-efficacy. However, there was no effect of either gender or educational level on the two dependent measures. The researchers recommend that there should be an increase the awareness of society as a whole about the importance of religious practices in addition to giving particular attention to ill people through special programs and well-planned and operated activities and trainings.